El liderazgo del mundo y América Latina - Roggero, Angelina (1967)
This deals with the very up-to-date theme of the change in world leadership and its consequences in the under-development countries. The basic thesis belongs to Prof. Dr. Wilhelm FUCKS, who recently wrote a paper on the outcome of population, economy and potentials as foreseen for the year 2040. Hence, the population, the production of food, energy and steel, are the bases for determining the potential of a country. Therefore those countries that have a big population with a poor industrial development will play no part on the international stage with relation to the potential of power. The meaning of this sentence when inverted is also valid. To this must be added the building-up of atomic power, and the modern chemical-biological arms. Then, as the industrial countries grow and become progressively richer, those which are agricultural will become more and more dependent on outside trade. Here, then, are the fundamental consequences facing the under-developed countries in particular Latin America.